Inventory System Analysis: A Case Study At Apotek Setia Farma, Bekasi - Lisye Ira Anne; Arief Bimantoro Suharko (CV. Syntax Corporation Indonesia, 2023)
This research was conducted aiming to determine the effect of motivation and compensation on employee performance mediated by organizational citizenship behavior at Sinergia Group Indonesia. This research was conducted because it saw the phenomenon of declining employee performance at Sinergia Group Indonesia. Employee performance can be influenced by factors such as personal factors, leadership factors, team factors, system factors, contextual/situational factors. The sampling method used is saturated sampling, because the entire population is used as a sample. This study used a sample of 40 people, using multiple linear regression techniques, path analysis and causal steps. The conclusions of this study are (1) the variable of motivation has a positive and significant effect on organizational citizenship behavior, (2) the variable of compensation has a positive and insignificant effect on organizational citizenship behavior, (3) motivation has a negative and insignificant effect on employee performance, (4) compensation variables have a positive and insignificant effect on employee performance, (5) organizational citizenship behavior variables have a positive and significant effect on employee performance, (6) organizational citizenship behavior variables are able to fully mediate the influence between motivational variables on employee performance, (7) organizational citizenship variables behavior is able to fully mediate the influence between compensation variables on employee performance.